Gambaran Tingkat Kecemasan Pasien Praoperasi Nefrolitotomi: A Description of Preoperative Anxiety Levels Among Patients Undergoing Nephrolithotomy - Cintia Febriyanti; Suyanto; Mohammad Arifin Noor (Universitas Ngudi Waluyo, 2026)
Preoperative anxiety is a psychological response commonly experienced by patients prior to undergoing surgical procedures, including nephrolithotomy. Anxiety that is not adequately managed may affect patients’ physiological conditions and influence their readiness to undergo surgery. This study aimed to describe the level of anxiety among patients in the preoperative phase of nephrolithotomy. This study employed a quantitative approach with a descriptive design. The sample consisted of 70 preoperative nephrolithotomy patients selected using purposive sampling. Anxiety levels were measured using the Amsterdam Preoperative Anxiety and Information Scale (APAIS). The collected data were analyzed using univariate analysis. The study results showed that most patients scheduled to undergo nephrolithotomy experienced moderate anxiety with an average score of 15,26.